Fast food : the transport of particulate organic matter over an upwelling event on the west coast of southern Africa - Biccard, Aiden (Department of Biological Sciences, 2017)
Differences in transport, composition and supply of particulate organic matter (POM), as a food source for coastal consumers, were investigated between an exposed headland (Cape Columbine) and a sheltered bay (Elandsbaai) in the southern Benguela. Physical data, in agreement with previous studies, showed that Cape Columbine is situated within an upwelling center and Elandsbaai within an upwelling shadow. Three distinct oceanographic conditions, upwelling, relaxation and downwelling, were discemable from wind, current and temperature data at each site. Upwelling was most prevalent at Cape Columbine in contrast to relaxation at Elandsbaai. Significant differences (P < 0.00001) in chlorophyll a concentration, quantities of organic carbon and % kelp-derived carbon were found between the two sites. In addition, significant differences (P < 0.0001) in chlorophyll a concentration, quantities of organic carbon and % kelp-derived carbon were found between the different oceanographic conditions: upwelling, relaxation and downwelling. A significant interaction (P < 0.00001) for % kelp-derived carbon was found between site and oceanographic conditions. Tests within study sites revealed significantly higher chlorophyll a concentrations in the euphotic zone, as expected. Furthermore, chlorophyll a concentrations showed a significant decrease with distance offshore at Elandsbaai. Percentage contribution of kelp-derived carbon (max = 36%) to POM was lower than predicted and surprisingly lower than values reported in previous works (77%). No stratification of kelp-derived matter or organic carbon was observed in the water column at both sites. It is likely that sampling stations were too shallow i.e. water column was well mixed as a results of nearshore turbulence. In terms of food supply to coastal consumers, upwelling episodes at Cape Columbine resulted in significantly high import of kelp matter into the nearshore water column. In contrast, phytoplankton, constituted the primary food source for both sites during relaxation and downwelling episodes. It is clear that different oceanographic conditions between an exposed headland and a sheltered bay have profound implications regarding the transport, composition and supply of POM, as a source of food to coastal communities.